Effects of Solution History on Sol‐Gel Processed Tin‐Oxide Thin‐Film Transistors. Issue 12 (24th August 2016) - Boratto, Miguel H.; Scalvi, Luis V. A.; Goncharova, Lyudmila V.; Fanchini, Giovanni
Abstract : Antimony‐doped tin‐oxide (SbTO) thin films deposited by solution processing methods represent a promising avenue toward low‐cost transparent and flexible electronics, but reproducibility and performance homogeneity of devices prepared from these thin films have been seldom investigated. In this study, the role of sol‐gel precursor aging is investigated by comparing SbTO thin‐film transistors (TFT) fabricated from two different sol‐gel solutions: the first one was aged for 4 years, whereas the second was prepared freshly. For each of the solutions, a set of TFT was assembled on the same chip, to investigate the distinct roles of aging and sample inhomogeneity on the electronic and transport properties of SbTO. Higher electron mobility, but lower on/off ratios, was found in TFTs assembled from freshly prepared solution, an effect that may be assigned to larger size of SbTO grains. This study demonstrates the critical role of the solution "history" in determining the properties and reproducibility of SbTO TFTs, over other factors, including local film inhomogeneity and local fluctuations of the annealing temperature.